Understanding social media - Hinton, Sam (Lecturer in media); Hjorth, Larissa (Los Angeles : SAGE, 2013)
'Understanding Social Media provides a critical and timely conceptual toolbox for navigating the evolution and practices of social media. Taking an interdisciplinary and intercultural approach, this book provides a clear and concise explanation of the key concepts but also goes beyond specific brands, sites and practices to show readers how to place social media more critically within the changing media and cultural landscape. As an aid to understanding, key concepts in each chapter are illustrated by case studies to give real-world examples of theory in action. Cutting across the many dimensions of social media, from the political, economic and visual, this book explores the industries, ideologies and cultural practices that are increasingly becoming part of global popular culture. This book is essential reading for students of media studies and cultural studies.' -- Publisher's website.
Includes bibliographical references (pages 145-156) and index.
Keywords: Digital media -- Social aspects; Social media; Information society